2009
DOI: 10.1097/ccm.0b013e3181a00629
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental hemodynamic and inflammatory effects of microparticles originating from septic rats*

Abstract: Rats with sepsis induced by peritonitis exhibited a specific phenotype of MPs. Inoculation of sMPs in healthy rats reproduced hemodynamic, septic inflammatory patterns, associated with oxidative and nitrosative stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 29 publications
3
55
0
Order By: Relevance
“…Very recently, we found that rats with sepsis induced by peritonitis exhibit a specific phenotype of MPs, with MPs from leukocytes increased. Inoculation of these MPs in healthy rats reproduced hemodynamic, septic inflammatory patterns associated with oxidative and nitrative stresses in heart and aorta (12). Although septic MPs from humans (10) or rats (11) exert different effects in terms of oxidative and nitrative stresses in the aorta, they exhibit similar effects in the heart.…”
Section: Discussionmentioning
confidence: 97%
“…Very recently, we found that rats with sepsis induced by peritonitis exhibit a specific phenotype of MPs, with MPs from leukocytes increased. Inoculation of these MPs in healthy rats reproduced hemodynamic, septic inflammatory patterns associated with oxidative and nitrative stresses in heart and aorta (12). Although septic MPs from humans (10) or rats (11) exert different effects in terms of oxidative and nitrative stresses in the aorta, they exhibit similar effects in the heart.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with these diverse effects, the overall clinical impact of neutrophil-derived microparticles is uncertain. Circulating leukocyte and erythrocyte microparticles isolated from septic rats induced hemodynamic instability in normal rats (43). In contrast, nonplatelet microparticles isolated from humans with sepsis improved the vasoconstrictor response of murine aortic rings (31).…”
Section: Circulating Neutrophils During Systemic Inflammationmentioning
confidence: 99%
“…Similarly, injection of circulating MPs from septic rats into healthy ones induced the detrimental hemodynamic and inflammatory patterns of sepsis, associated with oxidative stresses, whereas MPs from healthy rats had no effect. 127 Overall, MPs are diverse and biologically active, providing another bridge between inflammation and coagulation. They are increasingly recognized as a diagnostic, prognostic, and therapeutic target for thrombotic and inflammatory/infectious disorders.…”
Section: Microparticlesmentioning
confidence: 99%